A kind of polymer ion gel fiber with high porosity and its preparation and application
By mixing polymer materials and ionic liquids and preparing them by air spinning, the problem of failing to prepare ultra-high porosity three-dimensional ion gel fibers in the existing technology is solved, and the preparation of high-porosity fibers is achieved and flexible. Areas such as wearable and flexible batteries offer new application prospects.
Patent Information
- Application Number
- CN202211669715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-25
AI Technical Summary
There are no related reports in the prior art that ionic liquids are added to polymer materials to process into three-dimensional ionic gel fibers with ultra-high porosity (porosity greater than 80%).
By uniformly mixing polymer materials, ionic liquids, spinning aids and solvents to prepare spinning dope, and using air spinning to prepare polymer ion gel fibers, we have achieved the preparation of ultra-high porosity three-dimensional ion gel fibers. .
The prepared three -dimensional ion gel fiber has more than 90%of the compressed performance, which is suitable for flexible wearable and flexible batteries, providing new application prospects.
Smart Images

Figure CN115928262B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a three-dimensional ion gel fiber with ultra-high porosity and a preparation method thereof, and belongs to the field of polymer composite materials. Background Art
[0002] Ionic liquids are usually composed of organic cations and inorganic (or organic) anions and are usually liquid at room temperature. Ionic liquids have the characteristics of low volatility, structural designability, physical and chemical stability, and harmlessness to health and the environment. The material formed by fixing ionic liquids on a solid matrix is called an ion gel. Due to its dual characteristics of ionic liquids and solid matrices, it shows good application prospects.
[0003] Polymer ion gel, a mixture of high molecular organic polymers and ionic liquids, is a solid mixture with a gel-like structure and ionic conductivity. Ionic gels with specific structures and properties can be formed by confining ionic liquids in a three-dimensional polymer network. Due to the presence of ionic liquids, polymer ion gels have many unique functions, such as conductivity, excellent electrochemical stability, stability of properties over a wide temperature range, antifreeze and antibacterial properties, etc., and have very wide applications in energy storage, sensing, 3D printing and biomedicine.
[0004] At present, there is no related report in the prior art on adding ionic liquid into polymer materials to process into three-dimensional ion gel fibers with ultra-high porosity (porosity greater than 80%). Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides an ion gel fiber and a preparation method thereof, which is prepared by air-jet spinning from polymer materials and ionic liquids in the presence of a spinning aid. The polymer material matrix provides excellent mechanical properties and stability, thereby producing ion gel fibers with ultra-high porosity and excellent compression performance, which have new application prospects in the fields of batteries and sensors.
[0006] The technical solution of the present invention:
[0007] The first technical problem to be solved by the present invention is to provide a method for preparing polymer ion gel fiber, the preparation method comprising: firstly mixing polymer material, ionic liquid, spinning aid and solvent evenly to form a spinning solution, and then preparing polymer ion gel fiber by air-spinning the spinning solution; wherein the solid content of the spinning solution is 10 to 30%.
[0008] Furthermore, the polymer material includes: polyurethane, polyamic acid, polyvinylidene fluoride or polyvinyl alcohol, etc. The polymer material serves as the matrix of the ion gel fiber and provides basic mechanical properties for the ion gel.
[0009] Preferably, the polymer material is polyamic acid or polyurethane; more preferably polyamic acid.
[0010] Furthermore, the ionic liquid includes: one of an imidazole ionic liquid, a piperidine ionic liquid, a pyridine ionic liquid, a quaternary amine ionic liquid or a quaternary phosphonium ionic liquid.
[0011] Preferably, the ionic liquid is an imidazolium ionic liquid or a quaternary phosphonium ionic liquid; more preferably, it is an imidazolium ionic liquid.
[0012] Furthermore, the spinning aid includes: polyacrylonitrile, polyvinyl pyrrolidone or polyethylene oxide, etc., to improve the spinnability of the spinning solution; different spinning aids are selected for different materials.
[0013] Furthermore, the solvent is selected from: N,N-dimethylformamide (DMF), tetrahydrofuran, acetonitrile or ethanol, etc.; the selected solvent can dissolve the spinning aid and the polymer material.
[0014] Furthermore, when the polymer material is polyamic acid, the mass of the ionic liquid accounts for 10-57% of the total mass of the solid, the mass of the spinning aid accounts for 18-40% of the total mass of the solid, the total mass of the solid = the mass of the polymer material + the mass of the ionic liquid + the mass of the spinning aid, and the solid content of the spinning solution is 12-27%. The solid content is the proportion of the total mass of the solid in the spinning solution.
[0015] Furthermore, the method for uniformly mixing the polymer material, ionic liquid, spinning aid and solvent to prepare a spinning solution is as follows: first, the polymer material solution and the ionic liquid are stirred and mixed at room temperature to obtain a precursor solution, then the precursor solution and the spinning aid solution are stirred and mixed, and finally, a degassing treatment is performed to obtain the spinning solution.
[0016] Furthermore, when the polymer material is polyamic acid, the preparation method of the polymer ion gel fiber is: first, polyamic acid, ionic liquid, spinning aid and solvent are evenly mixed to form a spinning solution, and then the spinning solution is subjected to air-spinning to obtain polyamic acid ion gel fiber, and finally imidization treatment is performed to obtain polyimide ion gel fiber.
[0017] Furthermore, when the polymer material is polyamic acid, the method for preparing the polymer ion gel fiber comprises the following steps:
[0018] 1) stirring the ionic liquid and polymer material solution at room temperature for 0.5 to 1 hour to obtain an ionic liquid / polymer material mixed solution;
[0019] 2) stirring the spinning aid and the solvent at room temperature for 2 to 5 hours to obtain a spinning aid solution;
[0020] 3) adding the spinning aid solution to the ionic liquid / polymer material mixed solution in step 1), and stirring the mixture at room temperature for 2 to 3 hours to obtain a spinning solution;
[0021] 4) preparing ion gel fiber by air-spinning the spinning solution obtained in step 3);
[0022] 5) The ion gel fiber obtained in step 4) is subjected to imidization treatment to obtain a stable high-porosity three-dimensional polymer ion gel fiber.
[0023] Furthermore, in the air-jet spinning method of step 4), the air flow pressure of the air jet is 0.05-0.5 MPa, and the distance from the air jet to the receiving device (receiving cage) is 10-25 cm.
[0024] Furthermore, the process of the air-jet spinning method in step 4) is as follows: adding the obtained spinning solution to an injection pump, the aperture of the needle is 0.05-0.4 mm, and the feeding rate of the spinning solution is 0.01-0.05 ml / min; the air flow pressure of the jet nozzle is set to 0.05-0.5 MPa, and the distance from the jet nozzle to the receiving device (receiving cage) is adjusted to 10-25 cm; after collecting for 0.5-1 h, the fiber is obtained; the obtained fiber is allowed to stand at room temperature for 1-5 h, and the solvent is completely evaporated to obtain a stable polymer ion gel fiber.
[0025] The second technical problem to be solved by the present invention is to provide the above-mentioned polymer ion gel fiber, which is prepared by the above-mentioned method.
[0026] Furthermore, the porosity of the polymer ion gel fiber is greater than 80%.
[0027] The third technical problem to be solved by the present invention is to point out the use of the above polymer ion gel fiber in sensors or batteries.
[0028] Beneficial effects of the present invention:
[0029] The present invention adds ionic liquid to polymer materials to achieve functionalization treatment, and then uses a simple air-spinning process to prepare ion gel fibers with ultra-high porosity (greater than 80%). The obtained three-dimensional ion gel fibers have a compressibility of more than 90% and are more susceptible to deformation than non-structural polymer materials. It has great application prospects in the fields of flexible wearables and flexible batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the air-spinning process of the present invention.
[0031] Figure 2 is a SEM image of the fiber structure obtained in Example 1 of the present invention; Figure 2It can be seen that the present invention obtains ion gel fibers with certain pores.
[0032] Figure 3 The SEM image of the fiber structure obtained in Example 1 of the present invention under loading / unloading state; Figure 3 It can be seen that the high porosity ion gel fiber of the present invention has excellent compressibility
[0033] Figure 4 is a mechanical performance diagram of the sensor obtained in Example 1 of the present invention; Figure 4 It can be seen that the addition of polymer materials makes the ion gel fiber structure of the present invention have excellent mechanical properties.
[0034] Figure 5 is the sensitivity performance diagram of the sensor obtained in Example 1 of the present invention; Figure 5 It can be seen that the introduction of high-porosity ion gel fiber structure significantly improves the sensitivity of the sensor.
[0035] Figure 6 The response time signal diagram of the sensor obtained in Example 1 of the present invention; Figure 6 It can be seen that the fiber structure with excellent mechanical properties can respond quickly to external pressure.
[0036] Figure 7 is a cyclic response stability performance diagram of the sensor obtained in Example 1 of the present invention; Figure 7 It can be seen that the high-porosity fiber structure of the present invention has excellent structural and signal stability and can remain stable after 9000 cycles. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing polymer ion gel fiber, the preparation method comprising: firstly, uniformly mixing a polymer material, an ionic liquid, a spinning aid and a solvent to prepare a spinning solution, and then preparing the polymer ion gel fiber by an air-spinning method from the spinning solution; wherein the solid content of the spinning solution is 10-30%. The solid content is the proportion of the total mass of solids in the spinning solution, and the total mass of solids = the mass of the polymer material + the mass of the ionic liquid + the mass of the spinning aid.
[0038] The present invention provides a method for preparing high-porosity polymer ion gel fibers, which can be implemented in the following specific manner: firstly, an ionic liquid is mixed into a polymer material solution and fully stirred to form a uniform precursor solution; then, a dissolved spinning aid is added into the precursor solution and fully stirred to obtain a spinning stock solution; finally, the spinning stock solution is added into an injection pump, micro-nano fibers are prepared by an air-spinning method, and the polymer ion gel fibers with a three-dimensional structure are collected by a collecting cage at a distance of 10 to 25 cm; and appropriate pre-compression is performed during the drying process to obtain a stable ultra-high-porosity three-dimensional ion gel fiber structure.
[0039] In the present invention, the ionic liquid acts as a functional filler in the polymer material to achieve functional treatment of the fiber; the polymer material serves as the structural matrix of the fiber, providing good mechanical properties for the three-dimensional structure, generally 2MPa to 8GPa; the spinning aid is to enhance the spinnability of the ionic gel and obtain a stable spinning effect.
[0040] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Example 1
[0042] The preparation steps of a three-dimensional polymer ion gel fiber with ultra-high porosity are as follows:
[0043] 1. Preparation of spinning solution:
[0044] 1) adding 0.49 g of 1-ethyl-3-methylimidazolium tetrafluoroborate ionic liquid to 1.5 g of polyamic acid solution, wherein the mass concentration of the polyamic acid solution is 18%, and stirring at room temperature for 0.5 to 1 h to obtain a mixed solution of ionic liquid / polyamic acid solution;
[0045] 2) adding 1 g of polyacrylonitrile to 9 g of N,N-dimethylformamide solvent and stirring at room temperature for 2 to 5 hours to obtain a spinning aid solution;
[0046] 3) adding 2.2 g of the spinning aid solution to the mixed solution of the ionic liquid / polyamic acid solution in step 1), and stirring at room temperature for 2 to 3 hours to obtain a spinning solution of the ion gel composite material;
[0047] 2. Preparation of ultra-high porosity three-dimensional polymer ion gel fibers:
[0048] 1) Add the spinning solution into a micro-injection pump, the pore size of the needle is 0.05-0.4 mm, and the solution feeding rate is 0.05 ml / min;
[0049] 2) The air flow pressure of the jet nozzle is set to 0.05-0.5 MPa, and the distance from the jet nozzle to the receiving cage is adjusted to 10-25 cm;
[0050] 3) After collecting for 0.5 to 1 hour, a three-dimensional ion gel fiber is obtained;
[0051] 4) The obtained gel fiber is placed in a muffle furnace for imidization treatment, and the heating program is: 80°C, keep warm for 0.5h, 100°C, keep warm for 0.5h, 150°C, keep warm for 0.5h, 200°C, keep warm for 0.5h, 250°C, keep warm for 0.5h, 300°C, keep warm for 1h; finally, a stable three-dimensional polymer ion gel with ultra-high porosity is obtained.
[0052] 3. Preparation of the obtained gel fiber flexible pressure sensor
[0053] The ultra-high porosity three-dimensional ion gel fiber is cut into a size of 1cm×1cm as the middle dielectric layer structure, and copper foil is used as the electrode layer on the upper and lower layers respectively; the three-layer structure is encapsulated with tape and connected with conductive wires to form a capacitive flexible pressure sensor.
[0054] The fiber obtained in Example 1 was characterized by scanning electron microscopy. Figure 2 As shown by Figure 2 It can be seen that the ion gel fiber obtained by the present invention has an ultra-high porosity of 95%, and the fiber diameter is 0.8 to 2 microns. The fiber structure is cut into samples of 0.7cm×0.7cm×0.9mm, and the porosity is tested and calculated using the drainage method. The formula P=[(V0-V) / V0]*100% is used for calculation, and V0=0.9cm 3 , drain 0.042 ml of water, and calculate the porosity P = 95.33%.
[0055] The mechanical properties of the fiber structure were tested using a mechanical universal tensile testing machine. The results are as follows: Figure 4 The LCR bridge and the mechanical universal tensile testing machine were tested simultaneously. The capacitance of the obtained flexible pressure sensor changes with pressure, reflecting the sensitivity signal of the obtained flexible pressure sensor, and the response time and cycle stability are shown in Figure 5 , Figure 6 and Figure 7 As shown in the figure, the sensitivity can reach 10kPa -1 Above, the response time is within 10ms, and under the cyclic pressure of 100kPa, it maintains high signal stability and structural stability.
[0056] Example 2
[0057] 1) Add 0.1 g of polyethylene oxide to 9.9 g of N,N-dimethylformamide solvent and stir at room temperature for 2 to 5 hours, and add 1.8 g of polyurethane particles to 8.2 g of N,N-dimethylformamide solvent and stir at room temperature for 2 to 5 hours;
[0058] 2) adding 0.49 g of 1-ethyl-3-methylimidazolium tetrafluoroborate ionic liquid to 1.5 g of polyurethane solution, stirring at room temperature for 0.5 to 1 h to obtain a mixed solution of ionic liquid / polyurethane solution;
[0059] 3) adding 1.5 g of the spinning aid solution to the mixed solution of the ionic liquid / polyurethane solution in step 2), and stirring the mixed solution at room temperature for 2 to 3 hours to obtain a spinning solution of the ion gel composite material;
[0060] 2. Preparation of ultra-high porosity three-dimensional polymer ion gel fibers:
[0061] 1) Add the spinning solution into a micro-injection pump, the pore size of the needle is 0.05-0.4 mm, and the solution feeding rate is 0.05 ml / min;
[0062] 2) The air flow pressure of the jet nozzle is set to 0.05-0.5 MPa, and the distance from the jet nozzle to the receiving cage is adjusted to 10-25 cm;
[0063] 3) After collecting for 0.5 to 1 hour, a three-dimensional ion gel fiber is obtained;
[0064] 4) Leave the gel fiber at room temperature for 5 to 10 hours to allow the solvent to completely evaporate, and obtain a stable ultra-high porosity gel fiber.
[0065] The fiber structure was cut into samples of 1cm×1cm×3cm, and the porosity was tested and calculated using the drainage method. The formula P=[(V0-V) / V0]*100% was used, V0=3cm3, 0.084ml of water was drained, and the calculated porosity was P=91.6%.
[0066] Comparative Example 1
[0067] 1) adding 0.7 g of 1-ethyl-3-methylimidazolium tetrafluoroborate ionic liquid to 1.5 g of polyamic acid solution, wherein the mass concentration of the polyamic acid solution is 18%, and stirring at room temperature for 0.5 to 1 h to obtain a mixed solution of ionic liquid / polyamic acid solution;
[0068] 2) adding 1 g of polyacrylonitrile to 9 g of N,N-dimethylformamide solvent and stirring at room temperature for 2 to 5 hours to obtain a spinning aid solution;
[0069] 3) adding 2.2 g of the spinning aid solution to the mixed solution of the ionic liquid / polyamic acid solution in step 1), and stirring at room temperature for 2 to 3 hours to obtain a spinning solution of the ion gel composite material;
[0070] 2. Preparation of ultra-high porosity three-dimensional polymer ion gel fibers:
[0071] 1) Add the spinning solution into a micro-injection pump, the pore size of the needle is 0.05-0.4 mm, and the solution feeding rate is 0.05 ml / min;
[0072] 2) The air flow pressure of the jet nozzle is set to 0.05-0.5 MPa, and the distance from the jet nozzle to the receiving cage is adjusted to 10-25 cm;
[0073] As a result, under the limited preparation parameters, the spinning solution of the samples could not form a fiber structure; the reason was that the ionic liquid content was too high and the spinning effect of the spinning solution could not meet the requirements of air-jet spinning.
[0074] Comparative Example 2
[0075] 1) adding 0.49 g of 1-ethyl-3-methylimidazolium tetrafluoroborate ionic liquid to 1.5 g of polyamic acid solution, wherein the concentration of the polyamic acid solution is 18%, and stirring at room temperature for 0.5 to 1 h to obtain a mixed solution of ionic liquid / polyamic acid solution;
[0076] 2) adding 1 g of polyacrylonitrile to 9 g of N,N-dimethylformamide solvent and stirring at room temperature for 2 to 5 hours to obtain a spinning aid solution;
[0077] 3) adding 1.5 g of the spinning aid solution to the mixed solution of the ionic liquid / polyamic acid solution in step 1), and stirring at room temperature for 2 to 3 hours to obtain a spinning solution of the ion gel composite material;
[0078] 2. Preparation of ultra-high porosity three-dimensional polymer ion gel fibers:
[0079] 1) Add the spinning solution into a micro-injection pump, the pore size of the needle is 0.05-0.4 mm, and the solution feeding rate is 0.05 ml / min;
[0080] 2) The air flow pressure of the jet nozzle is set to 0.05-0.5 MPa, and the distance from the jet nozzle to the receiving cage is adjusted to 10-25 cm;
[0081] As a result, under the limited preparation parameters, the spinning solution of the samples could not form a fiber structure; the reason was that too little spinning aid was added, and the spinning effect was poor under the influence of high-content ionic liquid, and a stable fiber structure could not be formed.
Claims
1. A method for preparing a polymer ion gel fiber, characterized in that: The preparation method comprises: firstly, mixing a polymer material, an ionic liquid, a spinning aid and a solvent uniformly to form a spinning solution, and then preparing the polymer ion gel fiber by an air-spinning method through the spinning solution; the polymer material is polyamic acid, the mass of the ionic liquid accounts for 10-57% of the total mass of the solid, the mass of the spinning aid accounts for 18-40% of the total mass of the solid, and the total mass of the solid = the mass of the polymer material + the mass of the ionic liquid + the mass of the spinning aid; the porosity of the polymer ion gel fiber is greater than 80%; the spinning aid comprises: polyacrylonitrile, polyvinyl pyrrolidone Ketone or polyethylene oxide; the solid content of the spinning solution is 10-30%; the process of the air-jet spinning method is: adding the obtained spinning solution to an injection pump, the aperture of the needle is 0.05-0.4mm, and the feeding rate of the spinning solution is 0.01-0.05ml / min; the air flow pressure of the jet nozzle is 0.05-0.5MPa, and the distance from the jet nozzle to the receiving device is adjusted to 10-25cm; after collecting for 0.5-1h, the fiber is obtained; the obtained fiber is allowed to stand at room temperature for 1-5h, and the solvent is completely evaporated to obtain a stable polymer ion gel fiber.
2. The method for preparing a polymer ion gel fiber according to claim 1, characterized in that: The ionic liquid includes: one of imidazole ionic liquid, piperidine ionic liquid, pyridine ionic liquid, quaternary amine ionic liquid or quaternary phosphonium ionic liquid.
3. The method for preparing a polymer ion gel fiber according to claim 1 or 2, characterized in that: The ionic liquid is an imidazole ionic liquid or a quaternary phosphonium ionic liquid.
4. The method for preparing a polymer ion gel fiber according to claim 1 or 2, characterized in that: The ionic liquid is an imidazole ionic liquid.
5. The method for preparing a polymer ion gel fiber according to claim 1 or 2, characterized in that: The solvent is selected from: N,N-dimethylformamide, tetrahydrofuran, acetonitrile or ethanol.
6. The method for preparing a polymer ion gel fiber according to any one of claims 1 to 2, characterized in that: The method for uniformly mixing polymer material, ionic liquid, spinning aid and solvent to prepare spinning solution is as follows: firstly, the polymer material solution and the ionic liquid are stirred and mixed at room temperature to obtain a precursor solution, then the precursor solution and the spinning aid solution are stirred and mixed, and finally, a degassing treatment is performed to obtain the spinning solution.
7. The method for preparing a polymer ion gel fiber according to any one of claims 1 to 2, characterized in that: The preparation method of the polymer ion gel fiber is as follows: polyamic acid, ionic liquid, spinning aid and solvent are uniformly mixed to prepare spinning solution, then the spinning solution is subjected to air-spinning method to prepare polyamic acid ion gel fiber, and finally imidization treatment is performed to obtain polyimide ion gel fiber.
8. The method for preparing a polymer ion gel fiber according to claim 7, characterized in that: The preparation method of the polymer ion gel fiber comprises the following steps: 1) Stirring the ionic liquid and polymer material solution at room temperature for 0.5 to 1 hour to obtain an ionic liquid / polymer material mixed solution; 2) Stirring the spinning aid and the solvent at room temperature for 2 to 5 hours to obtain a spinning aid solution; 3) adding the spinning aid solution to the ionic liquid / polymer material mixed solution in step 1), and stirring at room temperature for 2 to 3 hours to obtain a spinning solution; 4) preparing ion gel fiber by air-spinning the spinning solution obtained in step 3); 5) The ion gel fiber obtained in step 4) is subjected to imidization treatment to obtain a high-porosity three-dimensional polymer ion gel fiber.
9. The method for preparing a polymer ion gel fiber according to claim 8, characterized in that: In the air-spinning method of step 4), the air flow pressure of the air jet is 0.05-0.5 MPa, and the distance from the air jet to the receiving device is 10-25 cm.
10. A polymer ion gel fiber, characterized in that: The polymer ion gel fiber is prepared by the method according to any one of claims 1 to 9.
11. Use of the polymer ion gel fiber according to claim 10 in a sensor or a battery.
Citation Information
Patent Citations
Sensor dielectric layer and preparation method and purpose thereof
CN109827682A
Polyimide nanofiber sponge and preparation method thereof
CN113943980A
Flexible nano-film pressure sensor and preparation method thereof
CN114279601A